Evaluasi Hasil Rancangan Elemen Balok Sebuah Gedung Bertingkat Sesuai dengan SNI 2847-2013: Studi Kasus: Proyek Konstruksi Gedung Wiego Warehouse di Kota Medan - Manaraja, Reformasi; Hani, Sheila; Rini, Rini (Majalah Ilmiah METHODA, 2024)
The stages of development and establishment of a region involve several key elements that require attention, including the construction of buildings that take into account the surrounding environmental conditions. Beams are structural components that function to transfer loads from slabs to columns, acting as horizontal reinforcement frames for the building. They support floor loads and connect upper columns. The purpose of this study is to review the existing beam elements and perform a reanalysis. The technique employed involves a beam evaluation using the SNI 2847:2013 standard. The results indicate that the beam analysis calculations align with field observations. The compression reinforcement installed in the beam did not yield, categorizing the beam element as tension-dominated. The spacing of the installed flexural reinforcement in the beam is D10-200. Calculation reviews show that the tensile reinforcement comprises 14D25 and 4D25, while the total compressive reinforcement amounts to 12D25. Thus, it can be concluded that the structural design complies with the technical specifications outlined in the applicable SNI standards.